Drag Reduction with Polymer Mixtures in Pipes of Different Diameters - Gimba , M. M; Edomwonyi-Otu, L. C.; Yusuf, N.; Abubakar, A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Transporting crude oil and other fluid in pipelines of different sizes over long distances in process industries require high amount of energy which results to high cost of installing pumping stations and maintenance. Addition in part per million (ppm) of high molecular weight polymeric solution reduce such cost. The effect of pipe diameter, oil input volume fraction and flow rate (superficial velocity) on drag reduction (DR) in horizontal oil-waterflows was investigated in unplasticised polyvinylchloride (uPVC) horizontal pipe with two different pipe diameters (0.012 and 0.02 m IDs). The two liquids used were diesel oil (ρ = 832 kg/m3, µ = 1.66 cP) and water (ρ = 1,000 kg/m3, µ = 0.89 cP) as test fluids at ambient conditions (25°C, 1 atm). Partially hydrolyzed polyacrylamide (HPAM; magnafloc 1011), polyethylene oxide (PEO) and Aloe Vera Mucilage (AVM) separately, as well as mixture of HPAM-AVM and PEO-AVM at different oil input volume fraction (δo; 0,0.25, 0.5, 0.75 and 1) and flow rate (Q; 0.65, 1.28, 1.90 and 2.46 m3/hr) were used. The master solution of 2,000 ppm, 2,000 ppm and 20,000 ppm for HPAM, PEO and AVM respectively and their respective mixtures were used to achieve the required concentrations. Mercury U-tube manometer was used to measure the pressure drop. DR of 62%, 65%, 54% for HPAM, PEO and AVM; 69 and 71% for HPAM-AVM and PEO-AVM respectively at mixing ratio of 3:1 and 1:19 in 0.012 m ID. Also, DR of 58%, 62%, 43% for HPAM, PEO and AVM; 67% and 68% for HPAM-AVM and PEO-AVM respectively in 0.02 m ID were obtained at the same condition. The pressure drops observed in the smaller pipe (0.012 m ID) was higher than that of the larger pipe diameter (0.02 m ID). From the experimental results, DR decreased with increase in the pipe diameter at the same conditions. This result implies that, DR in oil-water pipeline flow is a function of oil input volume fraction, superficial velocity and pipe diameter